The Emergence of a Contemporary Repertoire for the Shō - Suzuki, Seiko; Mizuno, Mikako (Circuit)

(untitled) (Circuit, musiques contemporaines, 2022)
The shō has played an important role in the creation of Japanese cultural identity. In examining this issue, we show the emancipation of contemporary shō repertoire in the last three decades. We outline the process of the creation of the cultural identity of shō from a historical perspective, explaining the physical structure, music tradition, and contemporary shō music. Shō has unique names for each bamboo pipe and each harmony. The limited number of shō harmonies determines traditional sound images. Some contemporary composers have collaborated to create original repertoires for shō; Maki Ishii, Toshi Ichiyanagi, Cort Lippe, Motoharu Kawashima.